Keabsahan Klausul Pengesampingan Pasal 1813 KUHPerdata dalam Akta Notaris: Kajian Terhadap Kuasa Mutlak Dalam Peralihan Hak Atas Tanah - Rolland Victor Silubun; Nurul Fatwa Ali; Riris Cahaya Andini (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to evaluate the existence, legal validity, and consequences of clauses that waive Article 1813 of the Indonesian Civil Code (KUHPerdata) within Notarial deeds, commonly known as absolute power of attorney. In business and property transactions, this waiver is frequently utilized to create irrevocable powers of attorney based on the principle of freedom of contract under Article 1338. However, in the agrarian sector, this practice faces stringent statutory prohibitions. This research employs a normative juridical method with a conceptual and statutory approach, utilizing secondary legal sources. The findings indicate that while Article 1813 generally functions as optional law (regelend recht), its waiver for land rights transfers is strictly prohibited by Instruction of the Minister of Home Affairs Number 14 of 1982. The inclusion of such a waiver clause violates the lawful cause requirement under Article 1320 of the Civil Code, rendering the entire binding sale and purchase agreement (PPJB) null and void. Consequently, the authentic deed loses its perfect evidentiary weight and becomes legally flawed. Notaries who formulate such clauses are subject to civil liability under professional fault (beroepsfout) or tort (onrechtmatige daad). The study implies that Notaries must independently refuse to draft deeds containing absolute power clauses to protect economically weaker parties and maintain professional integrity.